2011
DOI: 10.1111/j.1399-3038.2010.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐digestible oligosaccharides reduce immunoglobulin free light‐chain concentrations in infants at risk for allergy

Abstract: Prebiotic oligosaccharides influence the intestinal microbiota and can positively modulate the infant's immune system. It was demonstrated that a special prebiotic mixture (Immunofortis(®)) of short-chain galacto-oligosaccharides (scGOS) and long-chain fructo-oligosaccharides (lcFOS) can reduce the cumulative incidence of atopic dermatitis (AD) in infants at risk for allergy as determined using the AD symptom score (SCORAD). Additionally, it was shown very recently that immunoglobulin free light-chain (Ig-fLC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 24 publications
1
26
0
2
Order By: Relevance
“…56 Prebiotics were shown to reduce immunoglobulin free lightchain concentrations in infants at risk for allergy. 57 Although a reduction of eczema was reported in infants, this effect was not consistent between studies and caution was advised in view of methodological concerns regarding included studies. 58 Shortterm enteral supplementation of non-human neutral and acidic OS during the neonatal period in preterm infants dids not decrease the incidence of allergic and infectious diseases during the first year of life.…”
Section: Prebiotics and Allergy And Atopic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…56 Prebiotics were shown to reduce immunoglobulin free lightchain concentrations in infants at risk for allergy. 57 Although a reduction of eczema was reported in infants, this effect was not consistent between studies and caution was advised in view of methodological concerns regarding included studies. 58 Shortterm enteral supplementation of non-human neutral and acidic OS during the neonatal period in preterm infants dids not decrease the incidence of allergic and infectious diseases during the first year of life.…”
Section: Prebiotics and Allergy And Atopic Dermatitismentioning
confidence: 99%
“…65 There were no significant differences between the synbiotic and the placebo group. 57 The same group showed that synbiotics prevented asthma-like symptoms in infants with atopic dermatitis. 66 At the same time, another group reported that a synbiotic combination of Lacto salivarius plus FOS is superior to the prebiotic alone for treating moderate to severe childhood atopic dermatitis.…”
Section: Prebiotics and Allergy And Atopic Dermatitismentioning
confidence: 99%
“…Mechanistically, IgG4 serves as a blocking antibody via competition with allergens for binding to IgE on the Fc ε receptors [62] and as an anti-inflammatory factor due to its dynamic Fab arm exchange resulting as a bispecific antibody with a substantially decreased capacity for cross-linking [63]. In addition, infants who received nondigestible carbohydrates (prebiotics) during the first six months of age had lower incidence of atopic dermatitis, which was linearly associated with lower levels of Ig-fLCs [64]. Taken together, the decreasing levels of allergen-specific specific IgE and/or Ig-fLCs as well as the increasing levels of allergen-specific IgG4 partly contribute to the development of tolerance.…”
Section: Cellular Immunity Upon Tolerance To Cow's Milk Proteinsmentioning
confidence: 99%
“…They also can stimulate IFN-γ and IL-10 production [18]. The particular scGOS/lcFOS preparation decreased kappa and lambda immunoglobulin levels in plasma of infants at high risk for allergy development in contrast to infants receiving placebo formula [19].…”
Section: Acidificationmentioning
confidence: 99%